2011
DOI: 10.1007/dcr.0b013e3181fec377
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Arm (Laparoscopic, Hand-Assisted, and Robotic) Matched-Case Analysis of Intraoperative and Postoperative Outcomes in Minimally Invasive Colorectal Surgery

Abstract: In this 3-arm case-matched series, the robotic approach results in short-term outcomes comparable to conventional and hand-assisted laparoscopic approaches for benign and malignant diseases of the rectum and rectosigmoid. With 3-dimensional visualization, additional freedom of motion, and improved ergonomics, this enabling technology may play an important role when performing colorectal procedures involving the pelvic anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 19 publications
8
34
0
Order By: Relevance
“…It has to be critically pointed out that the preoperative robotic system preparation time was always significantly longer, thereby prolonging the use of the operating theater [62]. The same observation was reported by Patel et al [63] upon comparing RALS, CL, and HALS, with similar short clinical results in all groups. The mortality rate was analyzed by Keller et al [52]; no differences were found and the study concluded that CL, RALS, and SILS enable high-quality colorectal surgery [52].…”
Section: Advanced Clinically Approved Laparoscopic Techniquessupporting
confidence: 65%
“…It has to be critically pointed out that the preoperative robotic system preparation time was always significantly longer, thereby prolonging the use of the operating theater [62]. The same observation was reported by Patel et al [63] upon comparing RALS, CL, and HALS, with similar short clinical results in all groups. The mortality rate was analyzed by Keller et al [52]; no differences were found and the study concluded that CL, RALS, and SILS enable high-quality colorectal surgery [52].…”
Section: Advanced Clinically Approved Laparoscopic Techniquessupporting
confidence: 65%
“…A meta-analysis of 32 studies examining robotic-assisted rectal surgery demonstrated a wide range of operative times for robotic proctectomy from 192-385 min and 158-197 min for laparoscopic proctectomy [57]. Patel et al [58] compared robotic colectomy to standard laparoscopy and hand-assisted laparoscopy and found that the operative time for the robotic approach was 237 ± 56.8 min. This was significantly longer than both standard laparoscopy (181 ± 52.5 min) and hand-assisted laparoscopic colectomy (158 ± 51.0 min).…”
Section: Discussionmentioning
confidence: 98%
“…Completeness of TME Positive circumferential margin Harvested lymph nodes laTME, % taTME, % p laTME, % taTME, % p taTME/roTME : laTME p Shorter LOS, less pain, and lower demand for analgesics result in faster convalescence after roTME. Several authors consider less tissue trauma in RS due to subtle retraction by robotic arms and fine dissection as a main reason for less pain and shorter LOS [22,54]. Overall, this underlines the safety and feasibility of colorectal RS.…”
Section: Resultsmentioning
confidence: 76%